Perfil socioeconômico dos Irmãos Terceiros do Carmo da Vila da Cachoeira na primeira metade do século XVIII: Socioeconomic profile of the Irmãos Terceiros do Carmo the Vilage of Cachoeira in the first half of the XVIII century (Revista de História da UEG (REVHIST), 2019)
Abstract: The present article is methodologically structured through the construction of the socioeconomic profile of a portion of the "irmãos terceiros" who made up the membership of the Venerável Ordem Terceira de Nossa Senhora do Monte do Carmo the vilaage of Cachoeira of the then Bahia captaincy in the first half of the  XVIII century. No sibling entry or annuity payment books were preserved of first half of seven hundred. Thus, we resorted to other sources that could remedy the evident gap in the archive of the Third Order of Carmo de Cachoeira.  In this sense, we collected ecclesiastical and judicial sources that informed the belonging of the confraternities, and it was possible to locate the names of 50 "irmãos terceiros" of that period.  We seek to reconstruct the existing specificities in the Order's social framework, which is, from the characterization of the group we will look for traces that provide a greater understanding about the profile of the "irmãos terceiros" and their possible implications in the local social scenario. In order to support the discussion, we resort to recent historiographical productions that help us to understand the social intricacies that constituted the relations of the "irmãos terceiros" with the colonial society, based on the social profile of its members.Keywords: Third Order. Socioeconomic profile. Sociability.